2010
DOI: 10.1212/wnl.0b013e3181fd6170
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of adjunctive ezogabine (retigabine) in refractory partial epilepsy

Abstract: This study provides Class II evidence that adjunctive EZG/RTG reduces the occurrence of partial-onset seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
197
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(210 citation statements)
references
References 36 publications
11
197
1
1
Order By: Relevance
“…Seizure-free rates counted from the time of randomization were low, as expected in a refractory population: 3.2% at 600 mg/day and 4.7% at 900 mg/day, not statistically different from the 1.2% placebo rate (17).…”
Section: Efficacysupporting
confidence: 50%
See 3 more Smart Citations
“…Seizure-free rates counted from the time of randomization were low, as expected in a refractory population: 3.2% at 600 mg/day and 4.7% at 900 mg/day, not statistically different from the 1.2% placebo rate (17).…”
Section: Efficacysupporting
confidence: 50%
“…In clinical trials, there were single reported cases of suicidal ideation and of psychosis (16). Sudden death rates did not exceed reported rates for individuals with refractory epilepsy (16,17,18).…”
Section: Safetymentioning
confidence: 85%
See 2 more Smart Citations
“…Efficacy for this first-in-class agent was demonstrated in phase III clinical trials (23,24). Safety issues associated with ezogabine include dizziness, somnolence, confusion, and fatigue, which are all common for CNS-acting drugs.…”
Section: Improve Antiseizure Therapies That Target Novel or Multiple mentioning
confidence: 99%